Artículo Cientifico - Modelo de gestión para la implementación Herramientas Tecnológicas en la Educación en Galápagos - Chávez Vilema, Leaderson Fredy (2013)
The Management Model theme for the implementation of technological tools in education was born due to the existing constraints in the province of Galapagos with the access to technology. Currently the technology is being used in all areas of this society, to name a few, in children's toys, at home, in business, production, research, agriculture, health, in education, etc. The use and benefits offered by technology are innumerable. The issue that concerns us technologyin education, is beginning to become a part of the society and in schools the art of computer is taught and depending on which of course the use of certain tools (programming, database is taught data, design, hardware, etc). But the goal of this management model goes further, is to achieve that teachers implement ICTs as support tools in the daily process of teaching and learning and not only to establish ICT as a subject in the educational PENSUM. Robert Kaplan and David Norton, suggest that the CMI (Balance Scorecard) is a management system or administrative system, which goes beyond the financial perspective that managers tend to assess for the progress of a company. In this view you can determine that this system was aimed at for-profit companies, but is currently being used in the public company and the development of this thesis found that it can be used in any field. In addition to this, the difference between the Balance ¿ScoreCard Methodology¿, the prospects raised by Kaplan and Norton and this thesis, goes in the same order and is trying to create a new perspective that is LEGAL. This new perspective is defined because of the specialty of Galapagos, by having its own legal rules, which would strengthen and facilitate the implementation of this model.